Cartilage Biomarkers Coll2-1 and Coll2-1NO2 Are Associated with Knee OA MRI Features and Are Helpful in Identifying Patients at Risk of Disease Worsening. (December 2021) - Hick, Anne-Christine; Malaise, Michel; Loeuille, Damien; Conrozier, Thierry; Maugars, Yves; Pelousse, Franz; Tits, Cédric; Henrotin, Yves
Objective: To assess the cross-sectional association between serum levels of Coll2-1 and Coll2-1NO2, two cartilage degradation biomarkers; the burden of magnetic resonance imaging (MRI) features and clinical outcomes; and to evaluate the predictive value of these biomarkers on progression. Design: A total of 121 subjects with knee osteoarthritis (OA) were followed during 1 year with pain, function, and MRI assessment (PRODIGE study). Type II collagen-specific biomarker Coll2-1 and its nitrated form Coll2-1NO2 were directly measured in serum using immunoassays at baseline and after 3-, 6-, and 12-month follow-up. Results: Serum Coll2-1 and Coll2-1NO2 were correlated with several baseline knee features quantified with Whole-Organ Magnetic Resonance Imaging Score (WORMS). Coll2-1 was significantly correlated with periarticular cysts/bursitis (ρ = 0.29, P < 0.01), subarticular bone attrition (ρ = 0.25, P = 0.01), subarticular cysts (ρ = 0.24, P = 0.02), and articular cartilage integrity (ρ = 0.23, P = 0.03) WORMS subscores for the whole joint as well as with the medial femorotibial joint sum score (ρ = 0.26, P = 0.01) and medial femorotibial joint cartilage (ρ = 0.23, P = 0.02). Coll2-1NO2 correlated with WORMS total score (ρ = 0.23, P = 0.02), WORMS scores in the patellofemoral (ρ = 0.23, P = 0.02) and medial femorotibial compartments (ρ = 0.21, P = 0.03), with osteophytes scores (ρ = 0.27, P < 0.01), subarticular cysts (ρ = 0.24, P = 0.019), and intraarticular loose bodies (ρ = 0.27, P = 0.007). Baseline Coll2-1NO2 was higher in subjects with a pain worsening (426.4 pg/mL [278.04-566.95]) as compared to non-progressors (306.84 pg/mL [200.37-427.84]) over 1 year (AUC = 0.655, P = 0.015). Conclusion: Serum cartilage biomarkers Coll2-1 and Coll2-1NO2 are associated with several knee OA features quantified with WORMS. Our study also shows that the baseline value of Coll2-1NO2 is positively associated with pain worsening.